Visual Identity Design for Mas Joko, the Auto Trader Efforts to Increase Brand Awareness - Lukas Sugiyanto; Dhani Agustinus; Ivan Budi Rianto (Jurnal Info Sains : Informatika dan Sains, 2026)
This research aims to redesign the Mas Joko Pedagang Oto logo and standardize its application through application media. The research method uses research and development with a descriptive approach. The design technique uses Designing Brand Identity while data collection is done by observation and interviews. The results of the redesign of "Mas Joko Pedagang Oto" have a visual identity that is more appropriate to the brand's vision and mission and specific scope and meaning according to the needs and objectives of the Mas Joko Pedagang Oto brand.